Multisystem Inflammatory Syndrome in Children (MIS-C) Associated with Novel Coronavirus (SARS-CoV-2) Infection: A Report on Two Cases (Journal of Armed Forces Medical College, Bangladesh, 2021)
We report two critically ill children (aged 5–8 years), presented with features of multisystem inflammatory syndrome in children (MIS-C) from January 1 to February 2, 2021 at a tertiary-care center (Combined Military Hospital) in Dhaka, Bangladesh. Both of the previously healthy children tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. Clinical presentations were similar in both with fever, gastrointestinal complaints, respiratory distress, rash, headache and myalgia. Laboratory values were high levels of C-reactive protein, D-dimers, B-type natriuretic peptide (Pro-BNP), troponin I and low albumin levels in both patients. Evaluations for other infectious diseases werenegative. Both the patients were critically ill, requiring admission to the pediatric intensive care unit (P-ICU) due to circulatory shock and needed inotropes. One of the patients had respiratory failure and required mechanical ventilation. Both patients received steroids, Intravenous Immunoglobulin (IVIG), Remdesivir, Tocilizumab. MIS-C is a recently recognized pediatric illness spectrum in association with SARS-CoV-2 infection. As for manifestations of COVID-19 infection and its consequences in children is myriad and knowledge about MIS-C is evolving, reporting is essential for better understanding of clinical clues of MIS-C and finding out a panacea through experience sharing.JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 76-79